2007
DOI: 10.1021/ac0713510
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of GC/TOF-MS-Based Metabolomics Data for Identification of Biochemically Interesting Compounds Using OPLS Class Models

Abstract: Metabolomics studies generate increasingly complex data tables, which are hard to summarize and visualize without appropriate tools. The use of chemometrics tools, e.g., principal component analysis (PCA), partial least-squares to latent structures (PLS), and orthogonal PLS (OPLS), is therefore of great importance as these include efficient, validated, and robust methods for modeling information-rich chemical and biological data. Here the S-plot is proposed as a tool for visualization and interpretation of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
937
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,085 publications
(943 citation statements)
references
References 32 publications
4
937
0
2
Order By: Relevance
“…The percentages of variance explained by the first and second components in the model are 23.6% and 16.0%, respectively. Variable importance in the projection (VIP) ranks the overall contribution of each variable (peak intensity) to the OPLS-DA model-variables with VIP > 1 were selected as differential signals [9] and [12]. Accordingly, we identified a total of 18 differential metabolites in our study using NIST library, and 11 of them were confirmed by standard compounds (Table 6).…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of variance explained by the first and second components in the model are 23.6% and 16.0%, respectively. Variable importance in the projection (VIP) ranks the overall contribution of each variable (peak intensity) to the OPLS-DA model-variables with VIP > 1 were selected as differential signals [9] and [12]. Accordingly, we identified a total of 18 differential metabolites in our study using NIST library, and 11 of them were confirmed by standard compounds (Table 6).…”
Section: Applicationmentioning
confidence: 99%
“…Metabonomic studies generate complex multivariate data that requires chemometrics for interpretation [6]. With unsupervised methods like principle components analysis (PCA) [7], and supervised methods such as partial least square (PLS) [8] and orthogonal partial least square (OPLS) analysis [9], researchers can obtain classification patterns and identify the compounds responsible for such patterns and grouping.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been made to test the reliability of multivariate models [38,39], hence the 6-round cross-validation in SMICA-P software was herein applied to validate the OPLS-DA model against over-fitting by precluding 1/6th of all the samples in each round. The crossvalidated OPLS-DA scores map depicts the between-class separation (t p ) and predictive ability (Q 2 Y) simultaneously [32]. Each individual in this map is represented by two spatial dots: one for model score value (t p ) and the other for cross-validated score value (t cv ).…”
Section: Multivariate and Univariate Statisticsmentioning
confidence: 99%
“…Variable selection is an important step in multivariate analysis that can apparently enhance our understanding and interpretability of multivariate models and commonly referred to VIP statistics, loading weights, and correlation coefficients [28][29][30]. However, the practical use of these methods relies mostly on the experimental designs and purposes (e.g., animal or human studies, biomarker identification or pathway analysis), the size of samples, and preference of researchers as well [31,32]. A strict approach for selecting significant and reliable variables should likely be a combination of multiple criteria.…”
Section: Introductionmentioning
confidence: 99%
“…CART or logistic regression may not perform best in the presence of large intra-group variation. In comparison, Orthogonal Projections to Latent StructuresDiscriminant Analysis (OPLS-DA), is a supervised discrimination method that can deal with large intra-group variation, and thus provide markers that can be interpreted straightforwardly (Bylesjo et al, 2006;Wiklund et al, 2008). In addition, the approach gives a prediction model that can be used to test unknown samples for the presence of the property of interest.…”
Section: Introductionmentioning
confidence: 99%